Validation of a cloud-based tele-stroke system reliability in determining national institutes of health stroke scale scores for acute ischemic stroke screening in the emergency department - Saban, Mor; Moskovitz, Anner; Ohanyan, Sona; Reznik, Anna; Ribo, Marc; Sivan-Hoffmann, Rotem (Frontiers in Neurology, 2022)
Background and Purpose - The National Institutes of Health Stroke Scale (NIHSS) is the most recommended tool for objectively quantifying the impairment caused by a suspected stroke. Nevertheless, it is mainly used by trained neurologists in the emergency department (ED). To bring forward the NIHSS to the pre-hospital setting, a smartphone-based Telestroke system was developed. It captures the full NIHSS by video, transmits it off-line, and enables assessment by a distant stroke physician. We aimed to compare the reliability of an NIHSS score determined by a neurologist from afar, using the platform with a standard NIHSS assessment performed in the emergency departments. Methods – A multi-center prospective study was conducted in two centers (Vall d’Hebron, Barcelona, and Rambam, Israel). Patients admitted to the ED with suspected stroke had a neurological exam based on the NIHSS, while being recorded by the system. A skilled neurologist rated the NIHSS according to the videos offline. The results were compared with the NIHSS score given by a neurologist at bedside. Results - A total of 95 patients with a suspected stroke were included. Overall intraclass correlation coefficient was 0.936 (0.99 in VdH and 0.84 in Rambam), indicating excellent and good reliability, respectively Conclusions - Remote stroke assessment based on the NIHSS, using videos segments collected by dedicated platform, installed on a standard smartphone, is a reliable measurement as compared with bedside evaluation.